Potential of Pterostilbene as an Antioxidant Therapy for Delaying Retinal Damage in Diabetic Retinopathy - Raquel Burggraaf-Sánchez de las Matas; Isabel Torres-Cuevas; Iván Millán; María del Carmen Desco; Candela Oblaré-Delgado; Miguel Asensi; Salvador Mena-Mollá; Camille Oger; Jean-Marie Galano; Thierry Durand; Ángel Luis Ortega (Antioxidants)
Chronic hyperglycemia is a major driver of neurovascular damage in diabetic retinopathy (DR), a leading cause of preventable blindness in adults. DR progression is often undetected until its advanced stages, with oxidative stress recognized as a primary contributor. In diabetes, oxidative stress disrupts retinal cellular balance, damaging proteins, DNA, and lipids, and triggering photoreceptor degeneration. Pterostilbene (Pter), a polyphenol with antioxidant properties, has demonstrated protective effects in DR animal models and was assessed in a pilot clinical study. DR patients treated with 250 mg/day of oral Pter showed a reduction in the development of retinal vascular alterations characteristic of the disease. Urinary analyses confirmed Pter’s role in reducing the lipid peroxidation of polyunsaturated fatty acids (PUFAs), including arachidonic and adrenic acids, indicators of oxidative damage in DR. Pter also improved the GSH/GSSG ratio, reflecting a restored redox balance. However, after six months without treatment, retinal damage indicators reappeared, highlighting the importance of sustained intervention. These findings suggest that Pter may help slow the progression of DR by protecting against oxidative stress and highlight the importance of implementing antioxidant therapies from the diagnosis of diabetes, although its long-term impact and the development of consistent biomarkers deserve more research to optimize DR management.